Piezo1 deletion enhances cross-priming of CD8+ T cells by tumor-infiltrating CD11b+ dendritic cells - Tyler E Miller; Phuong Nguyen; Suzanne L Tomchuck; Jay T Myers; Saada Eid; Muta Abiff; Melissa Bonner; Alex Yee-Chen Huang; David Askew; Vrishabhadev Sathish Kumar; Justin W A Garyu (Journal for ImmunoTherapy of Cancer)
Background Tumor-associated myeloid cells (TAMCs) are an abundant, phenotypically plastic cell population that is critical for initiating a robust antitumor response. To properly combat cancer cells, TAMCs must sense and transduce both soluble and vital biophysical cues imparted by the dense extracellular matrix (ECM) of the tumor microenvironment (TME). Despite ample research enumerating the deleterious effects of a primary tumor’s ECM on TAMCs’ functionality, few studies have evaluated the contribution of mechanosensitive cation channel(s) underlying these detrimental changes.Methods Our study aimed to evaluate the significance of the mechanosensitive cation channel PIEZO1 in TAMCs’ phenotype and effector functionality. To do so, we generated CD11b-conditional Piezo1 knockout mice, orthotopically inoculated them with rhabdomyosarcoma 76–9, an aggressive syngeneic rhabdomyosarcoma cell line, and evaluated tumor burden, pan-immune compartment changes, and intrinsic myeloid and lymphoid transcriptomic and functional changes.Results Genetic deletion of Piezo1 in CD11b-expressing cells significantly hindered primary and metastatic tumor burden. Intratumorally, we observe enhanced infiltration of CD11b+ dendritic cells (DCs) and CD8+, but not CD4+, T cells. This phenotype was driven by CD11b+ DCs that have undergone transcriptional changes related to improved antigen presentation and T cell activation. Despite being canonically inefficient cross-presenters in the wildtype state, Piezo1 KO CD11b+ DCs, specifically the cDC2A subpopulation, efficiently cross-prime CD8+ T cells on exposure to exogenous particulate antigens.Conclusions Here, we report for the first time an association between mechanosensation and cross-presentation by cDC2A cells. Our findings may be impactful to improving the continued development of DC vaccines whose success hinges on proper antigen processing and presentation to cytotoxic T cells in the TME.